I speak for the women : a story about Lucy Stone - McPherson, Stephanie Sammartino; Liedahl, Brian (Minneapolis : Carolrhoda, 1992)
Chronicles the life of the outspoken nineteenth-century supporter of women's rights.
Includes bibliographical references (p. 63-[64]).
School Library Journal.
Booklist.
Horn Book.
6.3
3-6
Keywords: Stone, Lucy, -- 1818-1893 -- Juvenile literature; Stone, Lucy, -- 1818-1893.; Stone, Lucy, -- 1818-1893.; Suffragists -- United States -- Biography -- Juvenile literature; Suffragists; Feminists; Women -- Biography; Suffragettes -- Biography; Feminists -- Biography; Women -- Biography; Suffragists; Feminists